THE INFLUENCE OF WORKLOAD, WORK MOTIVATION, COMMUNICATION ON JOB SATISFACTION AT PT. ARLENE JAYA MANDIRI IN CIKARANG - Mahanani, Zenita Dian; Turangan, Joyce A. (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to determine the effect of workload, work motivation, communication on job satisfaction at PT. Arlene Jaya Mandiri in Cikarang. The author in this study used quantitative descriptive research with a cross sectional method. The population in this study were employees of PT. Arlene Jaya Mandiri. Sample selection was carried out using a non-probability sampling method with purposive sampling technique. In this research there are criteria for selecting a sample of PT employees. Arlene Jaya Mandiri who has worked for at least 1 year, with a sample size of 150 respondents for this research. From the data obtained, data processing will be carried out via SmartPLS 4.0 software using the Structural Equation Modeling (SEM) method. The research results show through hypothesis testing that all independent variables have a positive effect on job satisfaction at PT. Arlene Jaya Mandiri in Cikarang.